Application of the 6D Hofstede Model in an Analysis of the Polish and Portuguese Business Culture - Siemiński, Marek; Andruszkiewicz, Katarzyna; Pinho, Tiago (Olsztyn Economic Journal, 2022)
Business management in a culturally diverse environment, that is acting in different business cultures, is one of the major challenges facing managers nowadays. Cultural differences among societies have been known to exist for ages, but a holistic view of their impact on the business culture in particular countries, development of cultural typologies and studies into the nature of interactions between the business and organisational culture date back to the 1980s. The acceleration of social, technological and demographic changes, a more rapid process of globalisation as well as some disturbances, such as the COVID-19 pandemic, the war in Ukraine or the intensifying rivalry between China and the United States of America, increase organisational uncertainty. Such changes require a new cultural sensitivity as well as new, modified systems of values. The objective of this study has been to determine and compare the Polish and Portuguese business cultures. To this end, the contemporary Polish and Portuguese business cultures have been analysed according to the 6D Hofstede model.